Engineered yeast for the efficient hydrolysis of polylactic acid. (June 2023) - Myburgh, Marthinus W.; Favaro, Lorenzo; van Zyl, Willem H.; Viljoen-Bloom, Marinda
Graphical abstract: Highlights: Recombinant S. cerevisiae produce high titres of fungal PLA hydrolases. Crude supernatant effectively hydrolyses PLA emulsions, powders and films. Enzyme hydrolysis resulted in release of 9.44 g/L lactic acid from 10 g/L PLA film. Extreme fragmentation and more than 40% weight loss of PLA films observed. Enzyme initially targets amorphous fraction before hydrolysis of crystalline region. Abstract: Polylactic acid (PLA) is a major contributor to the global bioplastic production capacity. However, post-consumer PLA waste is not fully degraded during non-optimal traditional organic waste treatment processes and can persist in nature for many years. Efficient enzymatic hydrolysis of PLA would contribute to cleaner, more energy-efficient, environmentally friendly waste management processes. However, high costs and a lack of effective enzyme producers curtail the large-scale application of such enzymatic systems. This study reports the recombinant expression of a fungal cutinase-like enzyme (CLE1) in the yeast Saccharomyces cerevisiae, which produced a crude supernatant that efficiently hydrolyses different types of PLA materials. The codon-optimised Y294[CLEns] strain delivered the best enzyme production and hydrolysis capabilities, releasing up to 9.44 g/L lactic acid from 10 g/L PLA films with more than 40% loss in film weight. This work highlights the potential of fungal hosts producing PLA hydrolases for future commercial applications in PLA recycling.